The Role of Digital Finance to Strengthen Financial Inclusion and the Growth of SME in Indonesia - Shofawati, A (KnE Social Sciences, 2019)
At this era, innovation in technology is one of the key success factor for business to strengthen the maturity life of product life cycle, included financial industry. Nowadays the need for speed in delivery of product or services included in financial services especially Islamic Financial Services is very important. Indonesia which have the unique topography which consist of many islands need the speed of product or service delivery especially for the Small and Medium Enterprise (SME) financing which is the fundamental of economy in Indonesia. This paper have purpose to describes the role of Digital Finance to Strengthen Financial Inclusion and the Growth of SME in Indonesia.This paper uses qualitative method. The result of this research is describe the model of the role of Digital Finance to Strengthen Financial Inclusion and the Growth of SME in Indonesia. Keywords: Digital Finance, Financial Inclusion, Growth of SME, Indonesia.